Harris Hawks Optimization Algorithm for reducing THD using ZVT-ZCT-based QRCC: A comparative approach - Nisha C. Rani; N. Amuthan (Measurement: Sensors, 2024)
This study proposes a novel solution to address harmonic issues in a Renewable Energy Resource System (RES) connected to the grid, using a Voltage Source Inverter (VSI) controlled by a QRCC based on Zero Voltage Transition and Zero Current Transition (ZVT-ZCT). We enhance system performance by integrating Harris Hawks Optimization (HHO) with the VSI. Key outcomes include evaluating the system's effectiveness in terms of voltage drop, current drop, real power, active power, and total harmonic distortion (THD). Notably, settling times for various converters are highlighted: 0.01 s for SEPIC, 0.008 s for CUK, 0.005 s for ZETA, and an impressive 0.0001 s for the Cascade converter. Under different operational conditions, open-loop operation yields a THD of 18.45%, reduced to 7.843% in closed-loop with PI controller. Optimization techniques further improve the system, achieving a low THD of 0.0549%. We emphasize the significance of MPPT-based INC-IR for cascade converters, resulting in a minimal switching loss of 0.38W, showcasing the system's efficiency in energy conversion.